Modified key size determination models for symmetric ciphers - Ibrahim, Subariah; Maarof, Mohd. Aizaini (2005)
Key is an important element in cryptographic algorithms since it is one of the parameters that determine the security level of the algorithms. The larger the key size, the better security the algorithm can provide. Debates on key sizes were discussed in many literature and documents of software vendors that provide cryptographic solutions. The aim of this paper is to determine the key size for symmetric ciphers, particularly the block ciphers. We employed Lenstra's and Blaze et al.'s recommendations for adequate key size and applied it to Lenstra's model with some enhancements. Our first proposed model includes a lifespan of information to be encrypted. We also proposed a second model which takes quantum computing into consideration. The key size computation using the first model shows that AES key sizes are adequate for various lifespan of information. However our second model shows that AES is not adequate to protect very long term information